The holotype of Leaia silurica Matthew, 1910, Pennsylvanian, Lancaster Formation, New Brunswick - Miller, Randall (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1995)
The conchostracan Leaia silurica Matthew, 1910 was reviewed by Copeland in 19S7 and a hypotype described and deposited in the collections of the Geological Survey of Canada. Matthew's holotype has been recovered during organization of the G.F. Matthew collection at the New Brunswick Museum.